2019
DOI: 10.1111/jfbc.12989
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of fermented selected barley extracts with Lactobacillus plantarum dy‑1 on the proliferation of human HT‐29 Cells

Abstract: The objective of this study was to understand the changes of nutrition constituents in extracts of four varieties of barley fermented with Lactobacillus plantarum dy‐1 (LFBEs) and to uncover the potential apoptosis‐related mechanism induced by LFBE to inhibit the proliferation of HT‐29 cells. The contents of total polysaccharide, polyphenol, and protein in the four LFBEs significantly changed as the fermentation time went by and exerted different inhibitory effects on the proliferation of HT‐29 cells. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…For example, we have identified the alterations of main polyphenols by HPLC method, in which the coumaric acid, vanillic acid, and ferulic acid were significantly increased after fermentation (Zhang et al., 2017). In addition, the molecular weight of proteins was obviously decreased with fermentation (Xiao, Bai, Zhang, Wu, & Dong, 2019). Thus, we speculated that the polyphenols and proteins were the main bioactive compounds attributing to FBWN's beneficial role in insulin resistance and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have identified the alterations of main polyphenols by HPLC method, in which the coumaric acid, vanillic acid, and ferulic acid were significantly increased after fermentation (Zhang et al., 2017). In addition, the molecular weight of proteins was obviously decreased with fermentation (Xiao, Bai, Zhang, Wu, & Dong, 2019). Thus, we speculated that the polyphenols and proteins were the main bioactive compounds attributing to FBWN's beneficial role in insulin resistance and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that 10% WB and BF diets were effective at attenuating adiposity gain in a diet-induced obese rodent model as well as preventing against the development of obesity and metabolic impairments commonly seen with HFD feeding. BF is high in soluble β-glucan, and the beneficial effects of β-glucan supplementation have been extensively reported [ 26 , 42 44 ]. WB, on the other hand, is mostly composed of insoluble fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Functional substances with antioxidant and immunomodulatory in cereals are associated with an anti-cancer effect [ 152 ]. Xiao Xiang et al found that the Lactobacillus plantarum fermentation of barley extract (LFBE) can significantly inhibit human colon cancer HT-29 cell proliferation, which has the effect of inducing apoptosis of the cancer cells [ 153 ]. Japanese scholars found that residues from Saccharomyces cerevisiae fermentation of barley Shochu had therapeutic effects on mice models of liver cancer cells.…”
Section: Health Benefits Of Fermented Cerealsmentioning
confidence: 99%